Powstanie i działalność trzeciego zakonu św. Franciszka z Asyżu w Sokołowie Małopolskim do roku 1939 - Walicki, Bartosz (Archiwa, Biblioteki i Muzea Kościelne, 2021)
At the tum of the 19,h and 20th centuries lots of religious communities were founded in the St John Baptist parish in Sokołów Małopolski. One of the most important was the Third Order of St Francis. Its foundation was preceded by many years of endeavours. The very idea was propagated by the inhabitant of Sokołów, Katarzyna Koziarz, who became the member of the secular family of Franciscan family in Rzeszów in 1890. Since then morę and morę people from Sokołów had joined the Tertiary. At the beginning of the 20“’ century those who took steps to popularize the Third Order were Katarzyna Koziarz in Sokołów, Maria Ożóg and Małgorzata Maksym in Wólka Sokołowska and Katarzyna Bąk in Trzebuska while the parish priests, Franciszek Stankiewicz and Leon Szado did little for this matter. The members of the Third Order got involved in lots of activities such as sup- porting the building of the church, providing necessary things for the church and making mass of- ferings. Serious steps to found the Third Order in Sokołów were taken by the parish priest Ludwik Bukała. He organized monthly meetings for the Third Order members. He also established contact with the Bemardine Father, Wiktor Biegus, who 27 April 1936 came to Sokołów and became ac- ąuainted with the tertiaries in the parish. The permission for the canonical establishment of tertiary congregation was granted 4 May 1936 by the ordinary of Przemyśl, Bishop Franciszek Bard. The official foundation of the congregation in Sokołów took place 24 May 1936. The local tertiaries chose St Ludwik as their patron. The congregation govemment was constituted at the first meeting. The parish priest became the director of the community and Katarzyna Koziarz was ap- pointed the superior. On the day of the foundation there were about 100 members. In the first three years of the existence of the Third Order there were 30 people who received the habits and 28 who were admitted to the profession. After the canonical establishment of the congregation, the tertiaries became morę active. They provided the church with sacred appurtenances and fumishings, as well as organising public adora- tion of the Holy Sacrament. They would also wash liturgical linens and adom altars. In 1937 they bought a chasuble with the image of St Francis, and in 1939 they donated a banner with the images of Mother of God and St Francis. In addition, the tertiaries founded their own library with religious books and magazines. The congregation gathered for meetings in the parish church every month. Besides, they had occasional private gatherings. In the first years of the existence of the congregation there were 19 meetings of the Counsel. There were also two visitations of the Sokołów congregation held by Father Cyryl from Rzeszów 11 July 1937 and 6 August 1939. The activities of the tertiaries were hindered by the outbreak of the Second World War.